Framing deformalisation in public international law. (2nd October 2015) - van Mulligen, Anne
Abstract : Prominent international lawyers have flagged a process of deformalisation as one of the main perils confronting public international law. The term 'deformalisation' is, however, used rather ambiguously. This paper maps the discourse so as to frame the normative stakes associated with deformalisation. First, it surveys the perils associated with the process. Secondly, it distils the core descriptive claims regarding deformalisation. Thirdly, it expounds upon the pivotal movement underlying these descriptive claims: the displacement of content-independent techniques of reasoning with content-dependent ones. The paper advances an understanding of law's formal dimension grounded in actors' dispositions to treat legal norms as having a normative standing apart from their content. To the extent that content-independent normativity is displaced by deformalisation, the value of the rule of law diminishes.